(untitled) (Bangladesh Journal of Pharmacology, 2019)
The present study was conducted to evaluate the nephroprotective effect of a medicinal herb Costus pictus against doxorubicin-induced toxicity. Rats were divided into six groups and treated with doxorubicin and ethanol extract of the C. pictus. Doxorubicin was administered intraperitoneally with a single dose (4 mg/kg) per week for three weeks. The extract (200 or 400 mg/kg) was administered orally for 4 weeks to two doxorubicin groups. Significant changes of the serum kidney markers, albumin, urea, uric acid and creatinine, and glutathione peroxidase, glutathione–S-transferase, catalase, superoxide dismutase, reduced glutathione and lipid peroxides in the kidney of doxorubicin-treated rat were observed. Histological features were also severely affected. However, biochemical and histological changes in the extract-treated rat were non-significant, showing that the herb is nephroprotective. The effects were comparable to the anti-oxidant vitamin E. Video Clip of Methodology: Histology Techniques: 12 min 6 sec: Click to watch